Legal Challenges of Harmonizing Smart Contract Regulations within the European Union - Vičius, Vytautas (Teisė, 2025)
This article evaluates the regulatory legal landscape of smart contracts within the EU and examines a few essential legal challenges related to the need to harmonize smart contract regulations across the EU. It starts with analysis of some legal and technical aspects of the smart contract term form and arrives at the conclusion that there is no universal and unified term that contains technical aspects of the smart contract. This creates legal uncertainty, as the currently existing legal frameworks in many EU member states are not equipped to address these characteristics of smart contracts.Another issue of importance is the varied approaches to smart contract regulation across the EU member states. The paper reveals that, currently, there is a spectrum of regulatory strategies from pioneering to conservative, and identifies the main obstacles to regulatory harmonization within the EU. Without a common legal framework, a smart contract deemed valid and enforceable in one state may not be recognized in another member state.Finally, the current EU legislation is not specifically designed for smart contracts. However, it impacts their regulation by addressing critical aspects of digital operations like data ownership, access and control. Thus, successful integration of smart contracts into the EU’s regulatory environment will require a concerted effort to address these complex challenges.
Keywords: blockchain technology; smart contracts; contract law; regulation of smart contract; European Union Law